SISTEM INFORMASI AKADEMIK DENGAN RFID BERBASIS SMS GATEWAY (STUDI KASUS DI SMK MUHAMMADIYAH 2 BOJA) - Arif Fahrudin (STEKOM PRESS, 2019)
Muhammadiyah 2 Vocational School does the teaching and learning process in Boja, besides it requires communication between the school with parents / guardians of students regarding information on student grades, tuition payments and student attendance still using conventional methods. This study aims to create an Academic Information System based on SMS Gateway based RFID. Academic Information System with RFID based SMS Gateway can monitor student academic activities at school and makes the delivery of academic information easier and more transparent.